Latest developments in molecular docking: 2010–2011 in review. Issue 5 (25th March 2013) - Yuriev, Elizabeth; Ramsland, Paul A.
<x xml:space="preserve">Abstract</x> The aim of docking is to accurately predict the structure of a ligand within the constraints of a receptor binding site and to correctly estimate the strength of binding. We discuss, in detail, methodological developments that occurred in the docking field in 2010 and 2011, with a particular focus on the more difficult, and sometimes controversial, aspects of this promising computational discipline. The main developments in docking in this period, covered in this review, are receptor flexibility, solvation, fragment docking, postprocessing, docking into homology models, and docking comparisons. Several new, or at least newly invigorated, advances occurred in areas such as nonlinear scoring functions, using machine‐learning approaches. This review is strongly focused on docking advances in the context of drug design, specifically in virtual screening and fragment‐based drug design. Where appropriate, we refer readers to exemplar case studies. Copyright © 2013 John Wiley & Sons, Ltd.